2020
DOI: 10.1101/2020.03.20.001032
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural Correlates of Positive and Negative Valence System Dysfunction in Adolescents Revealed by Data-Driven Parcellation and Resting-State Network Modeling

Abstract: Objective: Adolescence is a period of rapid brain development when symptoms of mood, anxiety, and other disorders often first emerge, suggesting disruptions in maturing reward circuitry may play a role in mental illness onset. Here, we characterized associations between resting-state network properties and psychiatric symptomatology in medication-free adolescents with a wide range of symptom severity.Methods: Adolescents (age 12-20) with mood and/or anxiety symptoms (n=68) and healthy controls (n=19) completed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…For instance, in individuals with treatment resistant depression, there was no evidence of an association between regional glucose metabolism of the sgCG and SI (Ballard et al, 2015); however, other studies have found that inflammation in this region is higher in individuals with SI compared to those without SI (Holmes et al, 2018). In a recent study examining graph metrics in depressed adolescents, certain organizational properties other than eigenvector centrality of the right sgCG were associated with depression severity (Gabbay et al, 2020). However, we did not find this region as part of the model predicting increased internalizing severity in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in individuals with treatment resistant depression, there was no evidence of an association between regional glucose metabolism of the sgCG and SI (Ballard et al, 2015); however, other studies have found that inflammation in this region is higher in individuals with SI compared to those without SI (Holmes et al, 2018). In a recent study examining graph metrics in depressed adolescents, certain organizational properties other than eigenvector centrality of the right sgCG were associated with depression severity (Gabbay et al, 2020). However, we did not find this region as part of the model predicting increased internalizing severity in our sample.…”
Section: Discussionmentioning
confidence: 99%